Radial artery pseudoaneurysm after transradial cardiac catheterization: A case presentation - Alejandra Blanco, MD; Shahab Shayesteh, MD; Linda Chi Hang Chu, MD; Elliot K Fishman, MD (Radiology Case Reports, 2020)
Cardiac catheterization through the radial artery has reduced the percentage of complications seen previously in the femoral approach. Computed tomographic angiography is a noninvasive technique that can accurately diagnose pseudoaneurysms and other vascular pathologies.A 93-year-old female presented to the emergency department with pain and swelling of her right distal arm and wrist after a transradial cardiac catheterization procedure, as part of a transcatheter aortic valve replacement evaluation for severe aortic stenosis.Angiography is the standard diagnosing technique for aneurysms and pseudoaneurysms, but it is an invasive procedure. We show this case in order to highlight the importance of computed tomographic angiography as a noninvasive approach in diagnosing uncommon complications in the clinical setting.